2010
DOI: 10.1007/s10681-010-0324-7
|View full text |Cite
|
Sign up to set email alerts
|

Rust-proofing wheat for a changing climate

Abstract: This paper offers projections of potential effects of climate change on rusts of wheat and how we should factor in a changing climate when planning for the future management of these diseases. Even though the rusts of wheat have been extensively studied internationally, there is a paucity of information on the likely effects of a changing climate on the rusts and their influence on wheat production. Due to the lack of published empirical research we relied on the few published studies of other plant diseases, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 77 publications
(111 reference statements)
0
35
0
1
Order By: Relevance
“…Actually, the disease has infected the wheat when it is visually observed. When conditions are wet during the season, the yellow rust spores are dispersed by the wind and can result in rapid disease development higher up the plant; and in neighbouring wheat crops (Chakraborty et al, 2011). Therefore, it is important to monitor and estimate the severity, especially on the early infection of seedlings.…”
Section: Discussionmentioning
confidence: 99%
“…Actually, the disease has infected the wheat when it is visually observed. When conditions are wet during the season, the yellow rust spores are dispersed by the wind and can result in rapid disease development higher up the plant; and in neighbouring wheat crops (Chakraborty et al, 2011). Therefore, it is important to monitor and estimate the severity, especially on the early infection of seedlings.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of other diseases in trees was also reduced at EC, e.g. Phyllosticta minima in Acer (McElrone et al 2005), nor was any change reported in the uredospore production per unit lesion area or in the disease progress of Puccinia striiformis (stripe rust) in FACE experiments (preliminary results, Chakraborty et al 2010).…”
Section: Discussionmentioning
confidence: 94%
“…Secondly, it may be due to repetition every year in the study area. Therefore, it becomes more vulnerable to fungi (Chakraborty et al, 2011).…”
Section: Management Strategiesmentioning
confidence: 99%